52 SHORT-TERM OUTCOMES OF RAMIE VERSUS TLE FOR LOCALLY ADVANCED ESOPHAGEAL CANCER AFTER NEOADJUVANT CHEMORADIOTHERAPY: A PROPENSITY SCORE-MATCHED ANALYSIS. (14th September 2020) - Guo, X; Jiang, H; Li, B; Sun, Y; Hua, R; Li, Z
Abstract:  : This study aimed to compare the short-term outcomes of esophagectomy (RAMIE) versus thoracolaparoscopic esophagectomy (TLE) for patients undergoing neoadjuvant chemoradiotherapy (nCRT) for locally advanced esophageal cancer in a propensity matched cohort. Methods: Data for consecutive patients receiving nCRT plus RAMIE or TLE were collected prospectively from February 2016 to December 2019. Baseline characteristics and perioperative outcomes of the RAMIE and TLE groups were retrospectively compared. Results: After propensity matching, 48 pairs were identified. The conversion rate to open thoracotomy was comparable in RAMIE and TLE (4.2% vs 6.3%, P = 1). Median operative time in RAMIE was significantly shorter than TLE (237 vs 271 min, P < 0.001). Compared with TLE group, the median number of dissected lymph nodes was higher in RAMIE group at the left recurrent laryngeal nerve (RLN) area [2 (1–3) vs 1 (0–2), P = 0.014], total RLN area [4.5 (2.0–7.0) vs 2.5 (1.0–5.0), P = 0.008], and thoracic area [10.5(7.0–16.0) vs 8.5(5.0–14.5), P = 0.049]. There was no significant difference in pneumonia, leakage, and vocal cord paralysis. Conclusion: Compared to traditional TLE, RAMIE can achieve more lymph nodes yield at the RLN region and shorter operative time for the patients undergoing nCRT with comparable postoperative outcomes.